Analysis of constraints and alternative solutions to the implementation of chemical practicums in several high schools in Medan - Gusti Rahman; Rizki Fitriani Nasution; Alfi Rizkina Lubis; Putri Novira; Lusyana Rahman; Ester Hartina Ria Sinaga; Puan Ibna Maghfirah Thaharah; Sri Nur Afrida; Retno Dwi Suyanti; Ayi Darmana; Saronom Silaban (Jurnal Pendidikan Kimia (JPKim), 2020)
The laboratory is a place to train students' skills in conducting demonstration, experimental and scientific development practices. The provision of complete laboratory tools and materials and good laboratory management will make learning chemistry run optimally, but some high schools still do not meet the standards of facilities and infrastructure in the laboratory. Therefore, the researcher tries to collect the problems and constraints in the implementation of the practicum and find alternative solutions to the problem solving based on literature review and expert opinion. This research is a qualitative study which is a case study research in several high schools in Medan. The instruments in this study were student questionnaire, teacher questionnaire, principal questionnaire and observation sheet using Likert scale analyzed using the percentage formula. the results of the analysis of case studies conducted in a number of high schools in Medan, it can be concluded that, the area of chemistry laboratories in several schools in Medan meets BSNP standards, but there are still science laboratories used for chemical laboratories. The results of the analysis of equipment and materials that support the implementation of the practicum after the presentation of X1 schools 76.36%, X2 schools 65.67% and X3 schools 87.27%. Keywords: Chemistry laboratory; Practicum; Equipment